Profile of Student’ Concept Understanding of Data Centering and Distribution Measures: A Study on Basic Statistics Course - Anggraheni, Fani Yunida; Rumiati, Lina (JURNAL JENDELA PENDIDIKAN, 2025)
This study aims to describe the profile of students' concept understanding of data concentration and distribution measures in the Basic Statistics course. The main focus of the research covers students' understanding of the concepts of mean, median, mode, range, variance, and standard deviation. This study used a descriptive qualitative approach involving nine students in the fourth semester mathematics education study program at STKIP Modern Ngawi who had taken the material. Data collection was carried out through open description dianostic tests and semi-structured interviews. Data analysis was carried out using data reduction techniques, data presentation and conclusion drawing based on the Miles and Huberman model, as well as data triangulation to increase validity. The results showed that students in the high category were able to solve problems correctly and provide good conceptual explanations. Medium category students can solve problems procedurally but do not understand the meaning of the concept thoroughly, while low category students show misconceptions and conceptual errors that are quite dominant. These findings indicate the importance of a learning approach that emphasizes not only procedures, but also conceptual understanding and contextual linkages.